Tips Tips and Tricks of Solving Mathetmatics Assignment Training about Partial Integral with Tanzalin Method at 1st Senior High School Jejangkit and 1st Senior High School Tamban - Ahmad Lazwardi; Akhmad Ilmi; Norhaliza Norhaliza (Comment: an International Journal of Community Development, 2020)
As the curriculum develops. Middle school mathematics material is increasingly being obtained. But there are still many students who still find it difficult to adapt. The aim of community service is to help students learn Partial Integral material using the Tanzalin Method. This dedication was held at SMAN 1 Jejangkit and SMAN 1 Tamban schools.This dedication method is by giving students training and demonstration to solve partial integral problems using the Tanzalin method. The result of this dedication is that more and more students understand partial integration techniques and the teachers feel very helped by this activity.